188k views
1 vote
F(x) = x3 – 2x + 6
g(x) = 2x3 + 3x2 - 4x + 2
Find (f – g)(x).

User Cerlin
by
5.6k points

2 Answers

2 votes

Answer:

- x³ - 3x² + 2x + 4

Explanation:

(f - g)(x) = f(x) - g(x)

f(x) - g(x)

= x³ - 2x + 6 - (2x³ + 3x² - 4x + 2) ← distribute by - 1

= x³ - 2x + 6 - 2x³ - 3x² + 4x - 2 ← collect like terms

= - x³ - 3x² + 2x + 4 ← in standard form

User Fazy
by
5.5k points
2 votes

Answer:

-x^3-3x^2+2x+4

Explanation:

Just calculate each coefficient of the polynomial separately.

x^3-2x+6-(2x^3+3x^2-4x+2) = (1-2)x^3+(0-3)x^2+(-2-(-4))x+(6-2) = -x^3-3x^2+2x+4.

User Yann Duran
by
5.7k points